2022
DOI: 10.3390/cancers14225545
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Approaches in Colorectal Cancer Screening and Diagnosis, Recent Updates and Future Perspectives

Abstract: Colorectal cancer (CRC) is common Cancer as well as the third leading cause of mortality around the world; its exact molecular mechanism remains elusive. Although CRC risk is significantly correlated with genetic factors, the pathophysiology of CRC is also influenced by external and internal exposures and their interactions with genetic factors. The field of CRC research has recently benefited from significant advances through Omics technologies for screening biomarkers, including genes, transcripts, proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 195 publications
(179 reference statements)
0
9
0
Order By: Relevance
“…Blood samples contain an array of measurable biomarkers – cfDNA, extracellular vesicles/exosomes, secreted proteins, lipids, metabolites, epigenetics, immune cells, microbes – all of which may be informative to CRC detection. An increasing number of studies continue to show differential expression of multi-omic biomarkers in CRC cases, compared to normal controls ( 55 ). A limitation to a multi-omic approach may be that incorporating numerous biomarker types into a singular platform may be methodologically difficult, though progress is being made using microfluidic systems.…”
Section: Evolving Strategies and Conclusionmentioning
confidence: 99%
“…Blood samples contain an array of measurable biomarkers – cfDNA, extracellular vesicles/exosomes, secreted proteins, lipids, metabolites, epigenetics, immune cells, microbes – all of which may be informative to CRC detection. An increasing number of studies continue to show differential expression of multi-omic biomarkers in CRC cases, compared to normal controls ( 55 ). A limitation to a multi-omic approach may be that incorporating numerous biomarker types into a singular platform may be methodologically difficult, though progress is being made using microfluidic systems.…”
Section: Evolving Strategies and Conclusionmentioning
confidence: 99%
“…administration) was found to block the TGF-β1-induced ERK1/2 signaling pathway via the adenosine A 2A receptor, leading to the alleviation of fibrosis caused by BLM ( Huang et al, 2016 ). In recent years, the targeted omics approach for biomarkers discovery has been an effective approach for evaluating the effectiveness and mechanisms of BA ( Ullah et al, 2022 ). In the study of Chang et al (2021) , the researchers administered 25–100 mg/kg BA to rat models with PF caused by BLM.…”
Section: The Protection Of Ba Against Respiratory Diseasesmentioning
confidence: 99%
“…Recent findings revealed that epigenetic alterations are more frequent than genetic alterations in CRC ( Okugawa et al, 2015 ). Currently, many groups focus on epigenetic studies on CRC to discover new biomarkers for diagnosis and develop new therapies ( Ullah et al, 2022 ). The application of natural products such as phytochemicals with anticancer effects can be considered as one of the approaches to target lncRNAs to treat CRC, which may increase the sensitivity of CRC cells additionally to the prevailing therapies.…”
Section: Introductionmentioning
confidence: 99%